Strategy to step on obstacle during cross-country race to minimize overuse injury risk - Emanuela H. Kang; David G. Wilson; Jan K. Petric; Sophia Ulman (PLoS ONE, 2026)
Background Overuse injuries are a major concern in high school endurance sports such as cross-country running. Methods This study explores how joint laxity, foot placement, and surface friction affect ligament strain during obstacle interaction, using an in-silico computer model simulating a “stepping on obstacle” scenario. Incorporating ground reaction forces and muscle activation, the model evaluates soft tissue responses across 27 cases—varying three levels each of joint laxity (none, medium, high), foot placement (central, medial, lateral), and surface friction (low, medium, high). Ligament strain was recorded at every millisecond and analyzed statistically. Results Foot placement is the dominant factor in minimizing ligament strain, with medial foot strikes yielding the lowest anterior tibiotalar ligament strain (11.5%), which increased by 1.75× and 1.73× in central and lateral strikes, respectively. Friction level showed a negative correlation with strain, reducing anterior tibiotalar stress from low to high friction. Joint laxity positively correlated with plantar fascia strain, with the medium laxity group experiencing more strain than the no-laxity group. Conclusion These findings suggest that medial foot placement and higher surface friction significantly reduce injury risk, providing biomechanical insight and practical guidance for safer running techniques in young endurance athletes.